2008
DOI: 10.1021/ie800303k
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Reactive Distillation Process for the Indirect Hydration of Cyclohexene to Cyclohexanol Using a Reactive Entrainer

Abstract: In the conventional process for cyclohexanol production, large amounts of energy are consumed and a considerable quantity of side products is formed. In addition, the process is inherently unsafe. The alternative process of cyclohexene direct hydration requires large amounts of catalyst to overcome kinetic limitations. This publication shows the feasibility of a new route from cyclohexene to cyclohexanol by means of reactive distillation using formic acid as a reactive entrainer. This allows overcoming kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 12 publications
1
47
0
Order By: Relevance
“…5 To overcome the main problem of the thermodynamic equilibrium limitation of the direct hydration reaction of cyclohexene, the indirect hydration of cyclohexene was born out, which is a two-step process using formic acid as a reactive entrainer. [6][7][8][9] In the rst step, cyclohexene react with formic acid to produce cyclohexylformate, which is an electrophilic addition esterication, 10 needing acid catalyst to increase the conversion rate of cyclohexene. In the second step, the ester readily hydrolyzes to produce cyclohexanol.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 To overcome the main problem of the thermodynamic equilibrium limitation of the direct hydration reaction of cyclohexene, the indirect hydration of cyclohexene was born out, which is a two-step process using formic acid as a reactive entrainer. [6][7][8][9] In the rst step, cyclohexene react with formic acid to produce cyclohexylformate, which is an electrophilic addition esterication, 10 needing acid catalyst to increase the conversion rate of cyclohexene. In the second step, the ester readily hydrolyzes to produce cyclohexanol.…”
Section: Introductionmentioning
confidence: 99%
“…In the second step, the ester readily hydrolyzes to produce cyclohexanol. Steyer et al 5,6,11 simulates the indirect hydration process using two distillation towers. Sulfonic-acid resin Amberlyst-15 catalyzed the esterication of cyclohexene with formic acid in the rst distillation tower, the hydrolysis of cyclohexyl formate occurred in the second column.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, due to the high complexity of the process, the operating window was limited by multiple steady states. [9][10][11] Therefore, it is of great significance to develop other efficient reaction routes without noble metal catalysts to obtain CHOL.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, indirect hydration of cyclohexene to CHOL can be realized via the hydrolysis of cyclohexene‐derived ester with the accompany of production of CHOL. Nevertheless, due to the high complexity of the process, the operating window was limited by multiple steady states [9–11] . Therefore, it is of great significance to develop other efficient reaction routes without noble metal catalysts to obtain CHOL.…”
Section: Introductionmentioning
confidence: 99%
“…Tung and Yu (2007) first recommended using a RDC-TRS for the separations of quaternary reacting mixtures with the most unfavorable ranking of relative volatilities (i.e., two reactants are the lightest and heaviest components and two products the light and heavy ones). Katariya et al, 2009, Steyer et al, 2008 mentioned that a reactive distillation column with multiple reactive sections might be favorable to the indirect hydration of cyclohexene to cyclohexanol with formic acid as reactive entrainer. Zhang et al (2015) suggested adopting feed splitting in the synthesis and design of RDC-TRS and demonstrated great improvement in steady-state performance due to the reinforcement of internal mass integration and internal energy integration between the reaction operation and separation operation involved.…”
Section: Introductionmentioning
confidence: 99%